Digital Marketing Strategy In Increasing Sales Case Study On A+ Toraja Clothing Screen Printing - Nelce Opang; Abedneigo C. Rambulangi; Mey E. Limbongan (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to determine the increase in sales of digital marketing strategies in the A+ Toraja Clothing business. The procedure for collecting data from this study is observation, interviews, dokumentation, interviews, dokumentation. The type of research using research methods which include 4 (four) things, namely interaktive and interesting content, mobile marketing ( marketing), digital marketing integration and sustainable marketing. The conclusion of this study is to increase sales to MSME actors implementing digital marketing strategies. Digital strategies to acquire consumers, build preferences, promote brands, increase profits.